Why Ecosystem Access Fails: MSME Resource Conversion in Eastern Indonesia - Jacline I. Sumual; George Kawung; Mauna Th.B. Maramis (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – Ecosystem programs widen access to training, finance, networks, and digital tools, but access does not explain how a resource enters daily work. This study examines resource conversion and where it stalls or changes path. Design/methodology/approach – The study used an abductive comparative multiple-case design. Fourteen MSMEs were screened and 13 cases from four provinces were retained. The evidence includes 35 interviews with owners, employees, partners, and ecosystem actors, totaling 34 hours and 43 minutes. Analysis combined case chronologies, incident coding, cross-case matrices, and negative-case checks. Findings/Results – Sustained conversion involved local translation and recombination, a delegated trial, and routine embedding. Informal networks sometimes offered another entry. Owner bottlenecks, low operational slack, poor task-technology fit, and fragmented support were associated with stalled or symbolic use. The fragile case showed that a working system may still fail when knowledge and authority remain concentrated. Originality/Value – Resource conversion is defined as the bounded work between access and a repeatable routine. It excludes acquisition, broad strategic reconfiguration, and firm performance itself. The model distinguishes core, alternative, failure, fragile, recovery, and feedback movements.